Sensory Characterization and Consumer Preference Mapping of Fresh Sausages Manufactured with Goat and Sheep Meat. Issue 7 (8th June 2015) - Paulos, Kátia; Rodrigues, Sandra; Oliveira, António Filipe; Leite, Ana; Pereira, Etelvina; Teixeira, Alfredo
Abstract The main objective of this study was the sensory characterization, by a taste and a consumers' panel, of fresh sausages from 140 culled goats and 140 culled ewes. Species and type of preparation effects were studied. All data were previously analyzed by analysis of variance. Taste panel data were analyzed by a Generalized Procrustes Analysis (GPA). Consumers' panel data were analyzed by Preference Mapping. The 1st 2 factors explained 88.22% of total variation in GPA. Different sausages samples were perfectly differentiated by assessors. Goat sausages have been considered harder, more fibrous, and less juicy than sheep sausages. The panelists observed that sheep sausages without paprika had greater intensity of flavor, tasted spicy, and had an off‐odor, while goat sausages with paprika were considered sweeter. Consumers' panel did not show any preference for the different types of sausages. This means that all types of sausages can have market opportunity.